F(x) = x^2 +3x + 5. For f( 3+h), put x = 3+h. F( 3+h)= (3+h) ^2 + 3 (3+h) +5 = 9 +h^2 + 6h + 9 + 3h + 5 = h^2 + 9h + 23. .
The equation y = 2x + 3 is a linear equation, and the equivalent equation of y = 2x + 3 is y - 3 - 2x = 0
<h3>How to determine the equal equation?</h3>
The equation is given as:
y = 2x + 3
Subtract 3 from both sides
y - 3 = 2x
Subtract 2x from both sides
y - 3 - 2x = 0
The above means that the equation y - 3 - 2x = 0 is equal to the equation y = 2x + 3
Hence, the equivalent equation of y = 2x + 3 is y - 3 - 2x = 0
Read more about equivalent equations at:
brainly.com/question/2972832
#SPJ1
Answer: -6/11
-4x - 2(8x + 1) = -(-2x - 10) Distributive Property
-4x - 16x - 2 = 2x + 10 Combine like terms
-20x - 2 = 2x + 10 Subtract 2x from both sides
-22x - 2 = 10 Add 2 to both sides
-22x = 12 Divide by -22 for both sides
x = -6/11 Answer!